A Brief Review on Dengu - Tanweer, Saquib; Khan, Mohd. Shahid; Khinchi, M. P.; Ansari, Ashiya; Gautam, Shubham (Asian Journal of Pharmaceutical Research and Development, 2019)
Globally important arboviral infection transmitted by the Aedes genus of mosquito.Endemic in more than 120 countries, particularly the Southeast Asian and Western Pacific regions, the Caribbean, Latin America, and some regions in the US, Africa, and Middle East.Severe dengue fever is characterised by marked thrombocytopenia, severe haemorrhage, plasma leakage leading to shock or fluid accumulation with respiratory distress, and severe organ impairment. Confirmatory tests include viral antigen or nucleic acid detection and serology. Difficult to distinguish clinically from Zika and chikungunya virus infections without diagnostic testing. A tetravalent vaccine has been approved in Mexico, making it the first vaccine to be licensed in the world for the prevention of dengue. Dengue viruses (DENVs) cause the most common arthropod-borne viral disease in man with 50–100 million infections per year. Because of the lack of a vaccine and antiviral drugs, the sole measure of control is limiting the Aedes mosquito vectors. DENV infection can be asymptomatic or a self-limited, acute febrile disease ranging in severity. The classical form of dengue fever (DF) is characterized by high fever, headache, stomach ache, rash, myalgia, and arthralgia. Severe dengue, dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS) are accompanied by thrombocytopenia, vascular leakage, and hypotension. DSS, which can be fatal, is characterized by systemic shock. Despite intensive research, the underlying mechanisms causing severe dengue is still not well understood partly due to the lack of appropriate animal models of infection and disease. However, even though it is clear that both viral and host factors play important roles in the course of infection, a fundamental knowledge gap still remains to be filled regarding host cell tropism, crucial host immune response mechanisms, and viral markers for virulence.